Spectrum of Changes in Anogenital Mammary-like Glands in Primary Extramammary (Anogenital) Paget Disease and Their Possible Role in the Pathogenesis of the Disease. (August 2017) - Konstantinova, Anastasia M.; Spagnolo, Dominic V.; Stewart, Colin J.R.; Kacerovska, Denisa; Shelekhova, Ksenya V.; Plaza, Jose A.; Suster, Saul; Bouda, Jiri; Kyrpychova, Liubov; Michal, Michal; Belousova, Irena E.; Kerl, Katrin; et al.
Abstract : To determine whether a subset of primary extramammary Paget disease (EMPD) may originate in anogenital mammary-like glands (AGMLG), the authors studied 181 specimens of EMPD, detailing alterations in AGMLG. The latter were identified in 33 specimens from 31 patients. All patients were women, ranging in age from 38 to 93 years (median, 65 y). In all cases, lesions involved the vulva and in 1 patient the perianal skin was affected. Histopathologically, AGMLG manifested changes identical to columnar cell change (CCC) (87.1%), usual ductal hyperplasia (22.6%), columnar cell hyperplasia (CCH) (9.7%), oxyphilic (apocrine) metaplasia (6.5%), and atypical duct hyperplasia (3.2%). Four cases (12.9%), in addition to intraepidermal carcinoma, harbored invasive carcinoma. In all 4 of these, AGMLG displayed a range of alterations including ductal carcinoma in situ, CCC, and CCH. Three further cases (9.7%) showed ductal carcinoma in situ without any definite invasive carcinoma. Colonization of AGMLG by neoplastic Paget cells was noted in 6 cases. As CCC and CCH may be encountered in normal AGMLG, these alterations are unlikely to play a significant role in the pathogenesis of the disease. However, by analogy with mammary Paget disease, rare cases of primary EMPD may originate in AGMLG with a subsequent upward migration of the neoplastic cells into the epidermis and possible later breach through the basal membrane. Usual ductal hyperplasia and atypical duct hyperplasia can then be regarded as earlier precursor lesions, linking both ends of the spectrum.